Komunitas Muslim Minoritas: Problematika Migrasi dan Muslim Minoritas di Uni Eropa - Dianto, Icol (Jurnal at-Taghyir, 2020)
Abstract: The European Union is a destination country for immigrants from the Middle East and Africa. These immigrants seek protection (asylum) to the European Union because of conflicts in their home countries, both religious conflicts, political oppression, economic difficulties, and social unrest. This article aims to uncover the problems of the Muslim community as a minority group in the European Union. The author uses library research methods with a qualitative descriptive approach. The author found that the cause of Muslim migration to the European Union was due to conflict and war, economic crisis, and political oppression so they sought protection from the European Union. The election of the European Union as a destination country is because the European Union has opened itself to accept immigrants and is bound by international agreements so that the European Union has the responsibility to provide security protection for asylum seekers. The author also found that the arrival of immigrants to the European Union posed problems such as an immigrant identity crisis between national identity and citizenship identity, concerns of local European Union citizens over the issue of Islamization of Europe, fear of the threat of terrorism, and jealousy for Muslim immigrants because it was funded by EU member states. EU leaders are working to resolve this migration issue through joint financing between member countries and countries of origin of immigrants, equal distribution of immigrants, and strict selection of immigrants entering the European Union. Meanwhile, to solve the identity crisis, there are three models offered, namely integration, assimilation, and multiculturalism to create community inclusivism.Keywords: Muslim minorities, Muslim Europe, Muslim immigration, Islamophobia.Â Abstrak: Uni Eropa menjadi negara tujuan bagi para imigran dari Timur Tengah dan Afrika. Para imigran ini mencari perlindungan (suaka) ke Uni Eropa karena terjadi konflik di negara asalnya, baik konflik agama, penindasan politik, kesulitan ekonomi dan kerusuhan sosial. Artikel ini bertujuan mengungkap problematika komunitas muslim sebagai kelompok minoritas di Uni Eropa. Penulis menggunakan metode penelitian kepustakaan dengan pendekatan deskriptif kualitatif. Penulis menemukan bahwa penyebab migrasi muslim ke Uni Eropa karena terjadi konflik dan peperangan, krisis ekonomi dan penindasan politik sehingga mereka mencari perlindungan ke Uni Eropa. Terpilihnya Uni Eropa sebagai negara tujuan disebabkan Uni Eropa membuka diri untuk menerima kedatangan imigran dan terikat oleh perjanjian internasional sehingga Uni Eropa memiliki tanggungjawab untuk memberikan perlindungan keamanan bagi para pencari suaka. Penulis juga menemukan bahwa kedatangan imigran ke Uni Eropa menimbulkan persoalan yaitu krisis identitas imigran antara identitas kebangsaan dan identitas kewarganegaraan, kekhawatiran masyarakat lokal Uni Eropa atas isu islamisasi Eropa, ketakutan atas ancaman terorisme, dan kecemburuan kepada imigran muslim karena dibiayai oleh negara anggota Uni Eropa. Pemimpin Uni Eropa berupaya menyelesaikan isu migrasi ini melalui pembiayaan bersama antara negara anggota dengan negara asal imigran, pemerataan imigran, dan seleksi ketat terhadap imigran yang masuk ke Uni Eropa. Sementara itu, untuk menyelesaikan krisis identitas, ada tiga model yang ditawarkan yaitu integrasi, asimilasi dan multikultural untuk menciptakan inklusivisme masyarakat.Kata kunci: Muslim minoritas, Muslim Eropa, Muslim imigrasi, Islamophobia.